PENGARUH NILAI-NILAI BUDAYA GENERASI MILLENNIAL DAN BUDAYA SEKOLAH TERHADAP KETAHANAN INDIVIDU (Studi Di SMA Negeri 39, Cijantung, Jakarta) - Wahana, Heru Dwi (Jurnal Ketahanan Nasional, 2015)
This research aimed to knew characteristic of Generasi Millennialâs cultural values, cultural values influence Generasi Millennial and school culture to individual resilience in Country HIGHSCHOOL 39 Cijantungs Jakarta. Beside it was also to knew cultural correlation and values variable contribution Generasi Millennial and school culture variable to individual resilience. The result of research showed cultural values Generasi Millennial at high category, school culture at high category, and so do individual resilience at high category. Research also found that cultural values Generasi Millennial and school culture joinly (simultan) had strong correlation, positive and signifi can to individual resilience. And so do, cultural values of Generasi Millennial and school culture had signifi can infl uence to individual resilience, either independent and also along with (simultan).Keywords: Cultural Values of Generation of Millennial, School Culture, Individual Resilience.